La transnationalisation de l’industrie musicale de Miami - Alix Bénistant (Communication)
This article analyzes the emergence of a Miami music industry that specializes in the production, promotion, and distribution of “Latino” music. Using a socioeconomic approach, the author shows how, starting in the early 1980s, the Florida city gradually established itself as a hub for the development of a reified musical genre central to the “multiscalar” strategy of the dominant industry players.